Factors affecting cytoplasmic and nuclear structures of mouse gametes and embryos using immunocytochemistry technique / Nooraain Hashim - Hashim, Nooraain (2010)
Experiment 1 was conducted with the main objective to establish ICC technique for morphological analysis of the mouse oocytes and embryos in local laboratory. Several tests were conducted to achieve specific aims which included; a) to study efficacy of the available instruments and system for detecting fluorescence signals from mouse oocytes, b) to compare efficiency of improved methods to reveal oocyte morphology. Fluorescence images of the meiotic spindles, cortical granules and nuclear materials were compared between sample preparations methods. The results showed that the methods employed were reliable to be used for detecting the meiotic spindle, cortical granules and nuclear materials. The microdroplet method used in staining procedure produced high number of total oocytes recovered as compared with poly-l-lysine coated cover slip method. Meanwhile, the appearance of meiotic spindle in oocytes was significantly affected by the method used during samples preparation. A significantly higher percentage of clear meiotic spindles images were obtained from zona intact and methanol fixed oocytes, which were 62.8% and 64.7%, respectively (p<0.05). However, the images for cortical granules and nuclear materials were not significantly affected. The optimum range of titres of the fluorescent dyes used was equivalent to those reported by many laboratories. The non-specificity of the emission spectrum was detected in the present microscopy system. This was evidenced by images having both blue and green dyes overlapping each other, termed as cross-talk under the UV excitation filter. Hence, the quality of images obtained in fluorescence microscopy 140 depends greatly upon the methods employed in sample preparation and the system utilised for acquisition of images of the oocytes.